Recent advances in optical aptasensors for biomarkers in early diagnosis and prognosis monitoring of hepatocellular carcinoma - Dong, Jia-Mei; Wang, Rui-Qi; Yuan, Ning-Ning; Guo, Jia-Hao; Yu, Xin-Yang; Peng, Ang-Hui; Cai, Jia-Yi; Xue, Lei; Zhou, Zhi-Ling; Sun, Yi-Hao; Chen, Ying-Yin (Frontiers in Cell and Developmental Biology, 2023)
Hepatocellular carcinoma (HCC) accounts for approximately 90% of all primary liver cancers and is one of the main malignant tumor types globally. It is essential to develop rapid, ultrasensitive, and accurate strategies for the diagnosis and surveillance of HCC. In recent years, aptasensors have attracted particular attention owing to their high sensitivity, excellent selectivity, and low production costs. Optical analysis, as a potential analytical tool, offers the advantages of a wide range of targets, rapid response, and simple instrumentation. In this review, recent progress in several types of optical aptasensors for biomarkers in early diagnosis and prognosis monitoring of HCC is summarized. Furthermore, we evaluate the strengths and limitations of these sensors and discuss the challenges and future perspectives for their use in HCC diagnosis and surveillance.